Effectiveness of a personal health coaching intervention (diabetescoach) in patients with type 2 diabetes: protocol for an open-label, pragmatic randomised controlled trial - Oliver Faude; Fiona Streckmann; Lukas Zahner; Markus Gerber; Vivien Hohberg; Jan-Niklas Kreppke; Jan Kohl; Eleonora Seelig; Daniel König (BMJ Open)
Introduction The widespread prevalence of type 2 diabetes (T2D) not only influences patients’ daily lives but also has an economic impact on society. Increasing physical activity and a healthy diet can delay the progression of T2D. Although there are evidence-based recommendations on diet and physical activity, patients with T2D have difficulties implementing them. An appropriate lifestyle intervention can address this problem.Methods and analysis This study is based on the need to develop an intervention that helps patients to establish behavioural changes in order to achieve glycaemic control. The intervention will be evaluated in a monocentric, open-label, pragmatic, two-arm randomised controlled trial with a sample ratio of 1:1 and a parallel design. This superiority study will be conducted in Switzerland. All enrolled patients (n=90) will receive the standard medical treatment for T2D. The intervention group will receive personal health coaching by telephone and access to a smartphone and web application for 1 year. The control group will receive access to the application for 1 year and a one-time written diet and exercise recommendation. The primary outcomes are objectively measured physical activity and glycated haemoglobin. Secondary outcomes are self-reported physical activity, nutrition, cognitive mediators of changes in sport-related behaviour, blood values, medication and nutritional supplements, anthropometric data, quality of life, neuropathy and cost-effectiveness. All outcomes will be measured at baseline, at 27 weeks after inclusion and at 54 weeks after inclusion. The recruitment of participants and the measurements will be completed after 2 years. Linear mixed-effects models will be applied for each outcome variable to analyse the intervention effects.Ethics and dissemination This study was approved by the Ethics Committee North-western and Central Switzerland in February 2021 (ref: 2020-02755). All participants will be required to provide written informed consent. The results will be published in international peer-reviewed journals.Trial registration number ISRCTN79457541.